2016
DOI: 10.1042/bj20150734
|View full text |Cite
|
Sign up to set email alerts
|

PXR stimulates growth factor-mediated hepatocyte proliferation by cross-talk with the FOXO transcription factor

Abstract: Growth factor-mediated hepatocyte proliferation is crucial in liver regeneration and the recovery of liver function after injury. The nuclear receptor, pregnane X receptor (PXR), is a key transcription factor for the xenobiotic-induced expression of genes associated with various liver functions. Recently, we reported that PXR activation stimulates xenobiotic-induced hepatocyte proliferation. In the present study, we investigated whether PXR activation also stimulates growth factor-mediated hepatocyte prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…Recently, we have demonstrated that PXR activation accelerates CAR-dependent as well as growth factor-mediated proliferation of murine hepatocytes by increasing the sensitivity to proliferation stimuli through the downregulation of cyclin-dependent kinase inhibitor proteins (Shizu et al, 2013(Shizu et al, , 2016. We thus co-treated mice with TCPOBOP and imazalil to verify whether imazalil treatment could accelerate hepatocyte proliferation induced by TCPOBOP through mPXR activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have demonstrated that PXR activation accelerates CAR-dependent as well as growth factor-mediated proliferation of murine hepatocytes by increasing the sensitivity to proliferation stimuli through the downregulation of cyclin-dependent kinase inhibitor proteins (Shizu et al, 2013(Shizu et al, , 2016. We thus co-treated mice with TCPOBOP and imazalil to verify whether imazalil treatment could accelerate hepatocyte proliferation induced by TCPOBOP through mPXR activation.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA isolation and cDNA synthesis were carried out as described previously (Shizu et al, 2016). Quantitative RT-PCR (qRT-PCR) was performed using GoTaq qPCR Master Mix (Promega) and primer pairs for genes of interest shown in Supplementary Table S1.…”
Section: Determination Of Mrna Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, PXR has also been shown to play a role in promoting the growth and chemo-resistance of liver tumors (Braeuning et al, 2014; Rigalli et al, 2015). However, PXR over-expression portends a favorable prognosis in pancreatic adenocarcinoma (Koutsounas et al, 2015) but might aggravate liver tumors (Kodama and Negishi, 2011; Kodama et al, 2015; Shizu et al, 2015). PXR is also more recently implicated as a driver of DNA damage in cutaneous carcinogenesis (Elentner et al, 2015).…”
Section: Differential Role Of Pxr In Cancermentioning
confidence: 99%
“…PXR activation by PCNinhibits FoxO3-mediated transcriptional regulation of cell-cycle suppressor genes such as Rbl2 , thus promoting hepatocyte proliferation [97]. On the other hand, overexpressed FoxO3 inhibits the PXR-mediated enhancement of hepatocyte proliferation [97]. The regulation of hepatocyte proliferation by PXR has previously been reviewed by Pondugula et al [98].…”
Section: Regulation Of Pxr Through Protein-protein Interaction Andmentioning
confidence: 99%